2020
DOI: 10.19184/ams.v6i3.9840
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Duration of Sitting and Work Posture Risk with LBP in Library Staff University of Jember

Abstract: Low back pain (LBP) is one of the occupational diseases caused by non-ergonomic conditions. The global point prevalence of LBP which limits activity in 2015 was 7.3%. This figure shows that in one time there were 540 million people who experienced LBP. As many as 90% of cases of low back pain are not caused by organic abnormalities but by errors in body position at work. Risk factors that have the potential to cause complaints include age, gender, Body Mass Index (BMI), smoking habits, work period, poor work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…Judging from the phenomenon of office workers in sub-district X Bandung, it was found that the work posture was not good, plus most of the chairs were non-adjustable, starting from height, backrests, and related armrests. This study corrects the results of previous research by Cahyani, Hasan and Rumastika about the relationship between the risk of work posture and the incidence of low back pain Jember University Library Employees concluded that there was no relationship between the two [12]. This study confirms the results of the study Sumardiyono, Fajar and Mulyani with the title Relationship of Work Posture to Low Back Pain Complaints of Tea Pickers PT Perkebunan Tambi Wonosobo which concluded that there is a relationship between work posture and LBP complaints [13].…”
Section: Discussionsupporting
confidence: 87%
“…Judging from the phenomenon of office workers in sub-district X Bandung, it was found that the work posture was not good, plus most of the chairs were non-adjustable, starting from height, backrests, and related armrests. This study corrects the results of previous research by Cahyani, Hasan and Rumastika about the relationship between the risk of work posture and the incidence of low back pain Jember University Library Employees concluded that there was no relationship between the two [12]. This study confirms the results of the study Sumardiyono, Fajar and Mulyani with the title Relationship of Work Posture to Low Back Pain Complaints of Tea Pickers PT Perkebunan Tambi Wonosobo which concluded that there is a relationship between work posture and LBP complaints [13].…”
Section: Discussionsupporting
confidence: 87%
“…Based on data from the Institute of Health Metrics and Evaluation (IHME) in Western Europe in 2010 there were around 400,000-500,000 residents with LBP who were categorized based on the age range of 15-29 years. [2] There is no clear data for the incidence of low back pain in Indonesia, but according to the Ministry of Health in 2018, the prevalence of low back pain in Indonesia is 18% and will increase with age.According to the results of research conducted by Altinel in 2008, around 62% of adults experience LBP due to sitting for too long in the improper position. A person's sitting attitude at work will affect his/her work productivity, where while working with a proper sitting attitude, it will produce good productivity, vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…in the research measuring instruments. The work posture risk measurement tool in Cahyani et al's research used the Modified Quick Exposure Check (QEC) while LBP was measured using the LBP screening sheet 14. In another research conducted byKusumaningrum et al in 2021, 198 medical students also showed the same results.…”
mentioning
confidence: 89%
“…Hasan Sadikin Bandung. 13 Results of research conducted by Cahyani et al (2020) also stated that there is no significant relationship between the risk of work posture and LBP in library employees. 14 Research related to the relationship between work posture and the incidence of LBP in tailors was conducted by Syaputra et al (2022), with the results showing that there is a relationship between work posture and LBP complaints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation